Exploration of Local Wisdom in Land Dispute Resolution in Alor Regency - Rade, Stefanus Don; Lay, Benediktus Peter (Journal of Law, Politic and Humanities, 2025)
Land disputes are a common problem in rural areas that still rely on customary land inheritance without formal ownership documents. This study examines the mechanism of land dispute resolution based on local wisdom in South Pura Village, Pulau Pura District, Alor Regency, focusing on Tengtokung (diving ritual) as a form of alternative dispute resolution recognized by the local community. Referring to Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, this research adopts an empirical juridical method with statutory and legal anthropology approaches, as well as case studies of two land disputes that occurred in 2017 and 2019. Primary data were obtained through interviews with traditional leaders, village officials, and disputing parties, while secondary data were collected from literature studies. The results show that Tengtokung is conducted through a series of customary ceremonies involving community leaders, religious figures, and the families of the disputing parties, with outcomes considered final and fair by both sides. The strengths of this mechanism include its speed, low cost, confidentiality, and focus on restoring social relationships. However, its weaknesses lie in the absence of formal legal recognition and its reliance on the good faith of the parties, which may lead to future disputes. This study recommends strengthening the synergy between customary mechanisms and the national legal system to ensure legal certainty while preserving the community’s social harmony.